ANALISIS ASPEK KENYAMANAN JALUR PEDESTRIAN DI KAWASAN SCBD, JAKARTA SELATAN. (Studi Kasus : Jl. Senopati, SCBD, Jakarta Selatan) - Hantoro, Yovi Rizky Nurramadhanti; Khuluk, Nazaruddin (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2022)
The revitalized pedestrian path on Jl. Senopati, SCBD Area, South Jakarta, was builtwith the concept of a complete street. However, in mid-2022, many news stories were publishedthat the revitalized sidewalks were not well organized. This type of open pedestrian path,analyzed using the quality method to describe the current condition of the pedestrian path, as itis. The results of the observations are known from aspects that affect the comfort of pedestrianpaths, including circulation, facilities (street furniture), cleanliness, and safety. Aspect assessment on the 1.5 km pedestrian path is divided into 3 (three) segments. The results of the analysis seen from the circulation aspect get a very comfortable assessment, the facility aspect(street furniture), cleanliness, and safety, which is assessed according to theory, gettingcomfortable results. In addition, some points of the pedestrian lane area are still widely used asparking lots, stalls for street vendors who occupy pedestrian lanes, so it is necessary to reviewand rearrange pedestrian lanes so that, motorbikes and parked cars and street vendors can beput in order and do not endanger pedestrians, so that pedestrians can function properly